Effect of resistance exercise with bicycle’s inner tube on pulmonary function in women with metabolic syndrome - sawangjaithum, Kanokthip; Chittrakul, Jiraporn; Mongkol, Sarayoot (Journal of Associated Medical Sciences, 2017)
Background: Metabolic syndrome is often found in females and has effect on the pulmonary function whcih may induce to respiratory disease. Objectives: To examine the effect of resistance exercise with bicycle’s inner tube on pulmonary function in women with metabolic syndrome. Materials and methods: Twenty-five female volunteers aged between 30-50 years old were included to perform resistance exercise using a bicycle tire for 60 minute/day, 3 days/week for 8 weeks. Forced vital capacity (FVC), forced expiratory volume in one second (FEV1), FEV1/FVC ratio, and peak expiratory flow rate (PEFR) were measured at before and after 8 weeks of resistance exercise. Results: The results showed significant increase in FVC, FEV1, and PEFR (p<0.05), except for FEV1/FVC ratio after 8 weeks of resistance exercise compared to before exercise. Conclusion: The study suggests that 8-week resistance exercise with bicycle’s inner tube has an important role in improving pulmonary function, particularly FVC, FEV1, and PEFR in women with metabolic syndrome.